Changes in the incidence and mortality rates of malignant melanoma in the Seine-Maritime region over a 20-year period - Le Blanc, C; Corven, C; Courville, P; Duval-Modeste, A-B; Boivin, C; Ziadé, J; De Mauroy, C; Pellerin, A; Bokanowski, H; Dalibard, F; Gremain, J; Roquet, M-L; et al. (Annales de dermatologie et de vénéréologie, 2013)
The aim of this study was to assess changes in the incidence and mortality rates of malignant melanoma (MM) over a 20-year period in a region without a cancer registry. All cases of MM studied were collected retrospectively from the databases of six private and three hospital-based histopathology laboratories in the Seine-Maritime region covering three 24-month periods each 10years apart: 1988-1989, 1998-1999 and 2008-2009, The incidence and mortality rates were estimated based on data provided by French National Institute for Statistics and Economic Studies (Insee) and French National Institute of Health and Medical Research (Inserm). Over the 20-year period, the incidence of MM increased from 8.6 to 21.2/100,000inhabitants per year (+147%, P<0.0001) while the mortality rate rose from 1.3 to 2.8/100,000inhabitants per year (+115%, P=0.0003). The incidence of invasive MM increased by +110%, while the incidence of MM in situ increased by +456%. The incidence and overall mortality rate of invasive MM increased particularly during the first 10-year period: +62% (P<0.0001) and +77% (P=0.01) respectively, and to a much lesser extent during the last 10-year period: +30% (P=0.0007) and +22% (P=0.22) respectively. This slowdown in the incidence of invasive MM and in overall mortality rates was even more pronounced in women over the last 10years (+17 and +9%), whereas these rates continued to increase in men (+49% and +35%, respectively). In contrast, the incidence of MM in situ increased above all during this same period (+257%). This study shows that while the incidence and mortality rate of invasive MM has increased little over the last 10years in the Seine-Maritime region, the incidence of MM in situ continues to rise sharply.